ANALISIS HASIL BELAJAR SISWA MENGGUNAKAN MEDIA VISUAL PADA MATERI PERSAMAAN KUADRAT MENGGUNAKAN METODE RUMUS KUADRATIK - Anisa Nuralfiani; Luvy Sylviana Zanthy (IKIP Siliwangi, 2023)
Learning outcomes are changes in individual behavior which include the cognitive, affective, and psychomotor domains. Changes in behavior are obtained after students complete their learning program through interaction with various learning resources and learning environments. In this classroom action research, an analysis of student learning outcomes was carried out using visual media as teaching on quadratic equation material using the quadratic formula method for class IX students to determine the changes that occurred from the application of visual media in learning. The research was conducted by running two cycles with details in each cycle consisting of design, action and observation. The results obtained in the first cycle showed the value of student learning outcomes with an average of 57.7%, in the second cycle of learning with the use of visual media had an increase in learning outcomes to 73.3%. This increase was accompanied by an increase in other factors such as increasing student focus in understanding the material, as well as increasing student activity and courage in answering questions.